Facet nanoarchitectonics of visible-light driven Ag3PO4 photocatalytic micromotors: Tuning motion for biofilm eradication - Rojas Tizón, José Daniel; Kuthanová, Michaela; Číhalová, Kristýna; Pumera, Martin (NATURE PORTFOLIO, 2022)
The customized design of micro-/nanomotors represents one of the main research topics in the field of micro-/nanomotors; however, the effects of different crystal facets on micromotor movement are often neglected. In this work, self-propelled amorphous, cubic, and tetrahedral Ag3PO4 particles were synthetized using a scalable precipitation method. Their programmable morphologies exhibited different motion properties under fuel-free and surfactant-free conditions and visible light irradiation. Differences in these motion properties were observed according to morphology and correlated with photocatalytic activity. Moreover, Ag3PO4 micromotors are inherently fluorescent, which allows fluorescence-based tracking. Furthermore, bacterial biofilms represent a major concern in modern society since most of them are antibiotic resistant. The as-prepared self-propelled particles exhibited morphologically dependent antibiofilm activities toward gram-positive and gram-negative bacteria. The enhanced diffusion of the particles promoted biofilm removal in comparison with static control experiments, realizing the possibility of a new class of light-driven biofilm-eradicating micromotors that do not require the use of both H2O2 and UV light. Self-propelled amorphous, cubic, and tetrahedral Ag3PO4 micromotors were synthetized using a scalable precipitation method for antibacterial applications. Their programmable morphologies exhibited different motion properties under fuel-free and surfactant-free conditions and visible light irradiation. Differences in these motion properties were observed according to morphology and correlated with photocatalytic activity. Ag3PO4 micromotors are inherently fluorescent. The as-prepared self-propelled particles exhibited morphologically dependent antibiofilm activities toward eradication of gram-positive and gram-negative bacteria.

The customized design of micro-/nanomotors represents one of the main research topics in the field of micro-/nanomotors; however, the effects of different crystal facets on micromotor movement are often neglected. In this work, self-propelled amorphous, cubic, and tetrahedral Ag3PO4 particles were synthetized using a scalable precipitation method. Their programmable morphologies exhibited different motion properties under fuel-free and surfactant-free conditions and visible light irradiation. Differences in these motion properties were observed according to morphology and correlated with photocatalytic activity. Moreover, Ag3PO4 micromotors are inherently fluorescent, which allows fluorescence-based tracking. Furthermore, bacterial biofilms represent a major concern in modern society since most of them are antibiotic resistant. The as-prepared self-propelled particles exhibited morphologically dependent antibiofilm activities toward gram-positive and gram-negative bacteria. The enhanced diffusion of the particles promoted biofilm removal in comparison with static control experiments, realizing the possibility of a new class of light-driven biofilm-eradicating micromotors that do not require the use of both H2O2 and UV light. Self-propelled amorphous, cubic, and tetrahedral Ag3PO4 micromotors were synthetized using a scalable precipitation method for antibacterial applications. Their programmable morphologies exhibited different motion properties under fuel-free and surfactant-free conditions and visible light irradiation. Differences in these motion properties were observed according to morphology and correlated with photocatalytic activity. Ag3PO4 micromotors are inherently fluorescent. The as-prepared self-propelled particles exhibited morphologically dependent antibiofilm activities toward eradication of gram-positive and gram-negative bacteria.
Facet nanoarchitectonics of visible-light driven Ag3PO4 photocatalytic micromotors: Tuning motion for biofilm eradication
Keywords: surface; surface